PREDIKSI TINGKAT PENCEMARAN AIR SUNGAI MENGGUNAKAN INDEKS KIMIA-FISIKA DAN METRIK BENTIK MAKROINVERTEBRATA - Bahri, Syamsul (JURNAL SUMBER DAYA AIR, 2007)
Application of numeric benthic macroinvertebrate indices to predict river water pollution categories was poorly developed in Indonesia. A lack of information in this numeric indices study caused Indonesia be left behind in developing this science, consequently this method was not yet applied in routinely based river management. The main objectives of this research are: a). to examine the suitability of three benthic macroinvertebrate metrics to water chemical-physical index b). to assess test site based on water pollution categories. Survey method was used as research methodology. Water sampling and its analysis were done in field and laboratory. Standar Nasional Indonesia (SNI) was used as water quality analysis method. Scoring of LAWA was used to evaluate the chemical-physical index, whereas categorization and classification of water quality was based on the saprobic classification. As related to the correlation test, highest coefficient value was shown by score Biological Monitoring Working Party (BMWP) (r = 0,89) compared to a metric taxa richness (r = 0,84), and diversity index (r = 0,57). Therefore, BMWP score is indicating that classification of water pollution in Ciliwung River can be divided into three categories: moderately polluted, critically polluted and heavily polluted.